Perlindungan Hukum Fintech Leading Ilegal Berdasarkan Peraturan Otoritas Jasa Keuangan Nomor 77/Pojk.01/2016 - Diana Setiawati; Carisa Maharani; Latifah Kurniasih; Afifah Hapsari Afdah (Borobudur Law and Society Journal, 2022)
The shift to the era of the industrial revolution 4.0 resulted in changes in the field of digital technology that were relatively fast. One of the innovations in human life is innovation in financial services, namely Fintech Peer-to-Peer Lending (Lending). Based on data obtained from the OJK, throughout 2018-2021, there are as many as 3,516 illegal lending entities that have been stopped by the OJK. Therefore, in order to provide legal protection, OJK issued Financial Services Authority Regulation (POJK) Number 77 / POJK.01 / 2016 concerning Information Technology-Based Money Lending and Borrowing Services (LPMUBTI). The purpose of this study is to understand the development of Fintech Lending and legal protection for society of illegal Fintech Lending in Indonesia. In this study, researchers used juridical-normative research methods. Based on this research, researchers found that fintech lending has been developing for a long time in Indonesia and became a promising industry in 2015. The community is legally protected both preventively and repressively from illegal fintech lending practices.